Century 21 Jr. : input technologies & computer applications - Hoggatt, Jack, 1949-; Shank, Jon A.; Barksdale, Karl.; Rankin, Dianne S. (Australia : Thomson/ South-Western, 2006)
A variety of techniques related to computer applications in social studies, science, math, arts/literature, and the environment/health for middle school students are featured
Unit 1 : Digital communication tools -- Unit 2 : Keyboarding -- Unit 3 : Alternative input technologies -- Unit 4 : Word processing, desktop publishing, and document formatting -- Unit 5 : Computer applications
Includes index
Bound at top, portrait-style; paged continuously on rectos of pages from front to back, then on versos from back to front, with reference guide, glossary, and index following p. 305 in regular book pattern
Grades 5-9
Keywords: Keyboarding -- Problems, exercises, etc; Word processing -- Problems, exercises, etc; End-user computing; Computers -- Textbooks